2010
DOI: 10.1111/j.1547-5069.2010.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Factors Associated With Falls During Post‐Stroke Rehabilitation

Abstract: Purpose Our aims were to evaluate evidence of risk factors for falls among patients in stroke rehabilitation and to offer recommendations for clinical practice and future research. Method We conducted an integrative review of the literature published from 1990 to 2009 that describes empirical investigations of risk factors for post-stroke falls during inpatient rehabilitation. We searched Medline, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo, and Embase databases, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 37 publications
5
49
1
6
Order By: Relevance
“…Specific balance limitations identified during the evaluation will help determine the risk of falling and guide the selection and tailoring of balance-specific interventions. 308,591 Although balance training programs have been shown to be beneficial after stroke, no specific approach or program has been demonstrated to be superior, nor is the optimal timing clear. Balance training has been successfully implemented as group and one-on-one sessions, circuit training, and hospitalversus home-versus community-based programs.…”
Section: Balance and Ataxiamentioning
confidence: 99%
“…Specific balance limitations identified during the evaluation will help determine the risk of falling and guide the selection and tailoring of balance-specific interventions. 308,591 Although balance training programs have been shown to be beneficial after stroke, no specific approach or program has been demonstrated to be superior, nor is the optimal timing clear. Balance training has been successfully implemented as group and one-on-one sessions, circuit training, and hospitalversus home-versus community-based programs.…”
Section: Balance and Ataxiamentioning
confidence: 99%
“…Therefore, a number of studies have focused on fall prevention during inpatient stroke rehabilitation (Andersson et al 2006;Czernuszenko and Czlonkowska 2009). Campbell and Matthews (2010) reported that the falls during inpatient stroke rehabilitation was considered as potential risk factors of impairment of balance and self-care. In particular, a fall leads to the fear of falling again and sustaining serious injuries such as a hip fracture and head injury (Dennis et al 2002;Poole et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired balance increases the risk of falls [9], and may thus imply social problems and high economic costs [10].…”
Section: Main Textmentioning
confidence: 99%